Defective Pt–Ni/graphene nanomaterials by simultaneous or sequential treatments of organometallic precursors by low‐pressure oxygen plasma. Issue 5 (20th March 2019) - da Silva Pires, Mathieu; Haye, Emile; Zubiaur, Anthony; Job, Nathalie; Pireaux, Jean‐Jacques; Houssiau, Laurent; Busby, Yan
Abstract: A strategy to reduce critical raw metals in nanocatalysts is to synthesize nanocomposites based on defective or bimetallic nanoparticles deposition on carbon nanomaterials. Conventional solution‐based methods suffer from the extensive use of solvents and difficult scalability. In this study, defective Pt–Ni nanoparticles are formed on graphene nanoplatelets thanks to an original approach based on simultaneous or sequential low‐temperature oxygen plasma treatments of nickel and platinum acetylacetonates. The two processing conditions produce aggregated Pt–Ni nanoparticles with variable morphologies, size crystallinities, and oxidation states. The materials analytical characterizations show that the sequential treatment promotes small Pt–Ni particle aggregates nucleation, while the simultaneous treatment leads to complex interconnected Pt–Ni‐based phases. Such defective nanoparticles are promising for multiple applications in catalysis and energy. Abstract : Low‐pressure oxygen plasma discharges are applied to solid organometallic precursors for the synthesis of defective Pt–Ni nanoparticles on graphene nanoplatelets. The advantages are a scalable and solvent‐free methodology. The comparison between a sequential and simultaneous treatment of the two metal precursors allows varying the morphology, size and chemical state of Pt and Ni nanoparticles.